Human Wee1 kinase inhibits cell division by phosphorylating p34cdc2 exclusively on Tyr15. - McGowan, C H (1993)
In fission yeast, the M-phase inducing kinase, a complex of p34cdc2 and cyclin B, is maintained in an inhibited state during interphase due to the phosphorylation of Cdc2 at Tyr15. This phosphorylation is believed to be carried out primarily by the Wee1 kinase. In human cells the negative regulation of p34cdc2/cyclin B is more complex, in that Cdc2 is phosphorylated at two inhibitory sites, Thr14 and Tyr15. The identities of the kinases that phosphorylate these sites are unknown. Since fission yeast Wee1 kinase behaves as a dual-specificity kinase in vitro, a popular hypothesis is that a human Wee1 homolog might phosphorylate p34cdc2 at both sites. We report here that a human gene, identified as a possible Wee1 homologue, blocks cell division when overexpressed in HeLa cells. This demonstrates functional conservation of the Wee1 mitotic inhibitor. Contrary to the dual-specificity kinase hypothesis, purified human Wee1 phosphorylates p34cdc2 exclusively on Tyr15 in vitro; no Thr14 phosphorylation was detected. Human and fission yeast Wee1 also specifically phosphorylate synthetic peptides at sites equivalent to Tyr15. Mutation of a critical lysine codon (Lys114) believed to be essential for kinase activity abolished both the in vivo mitotic inhibitor function and in vitro kinase activities of human Wee1. These results conclusively prove that Wee1 kinases inhibit mitosis by directly phosphorylating p34cdc2 on Tyr15, and strongly indicate that human cells have independent kinase pathways directing the two inhibitor phosphorylations of p34cdc2.